O corpo, a ruina e o tempo : fotografia documental e arte na obra de Miguel Rio Branco - Brasil, Luisa Kuhl (2019)
This thesis presents a reflection on the images of the human body in the work of the brazilian artist Miguel Rio Branco (1946-). Looking for the contaminations among documentary photography and art, the work proposes an analysis of works of the artist from the ruin (of the human body and the landscape) and the relations with the multiple temporalities. The works are analyzed from different ways of exposure: the photographic series “Satelites” published in the Malasartes Art Magazine (1976), the exhibition “Negativo Sujo” placed in Parque Laje in 1978, the photobooks “Dulce Sudor Amargo” (1985) and “Silent Book” (1998), the exhibition and the movie Nada levarei quando morrer aqueles que mim deve cobrarei no inferno (1980), the “Barroco” polyptych (1994), the art installations “Diálogo com Amaú” (1983) and “Out of Nowhere” (1994). The aim of studying different media is the main restlessness: as the field of photodocumentarism, throughout the 1970s and 1980s, has undergone some changes, thus providing the creation of works that have in art and documentary photography substance for creation of hybrid poetics. We realize that the images of the human body in the work of Rio Branco are the common thread in the constitution of a poetic that has in documentary photography and in art its expression. Thus, the main objective of the work is to analyze the visual poetics of Miguel Rio Branco from the images of the human body, based on concepts related to ruin and temporality.